The effect of bottom ash on crushable sandy soil - Tan, Wai Hong (2018)
In construction, the breakage of sand particles are often occur under crushing load, for instance, during the pile driven process into the sand. The breakage of sand particle will result in the reduction of size of the sand and alter it engineering properties such as particle size distribution, particle shape, void ratio and many others properties. The objective of this research project is to study the effect of bottom ash on crushable sand soil. The effectiveness of bottom ash in improving the engineering properties of crushed sandy soil was studied. The bottom ash with 5%, 10%, 15% and 20% was added into the sand and crushed with 500 and 1000 blows under Automatic Compactor. The engineering properties of different proportion of bottom ash mixture before crushing and after crushing with 500 and 1000 blows were tested. The engineering properties which were tested including the sieve analysis, specific gravity, relative density, permeability test, standard proctor test and California bearing ratio test. Based on the result, the adding of bottom ash into the crushable sand showed improvement to the load bearing capacity of the crushable sand. The improvement includes the engineering properties such as crushability indices, bearing capacity and permeability.